Effectiveness of mixing poultry litter compost with rice husk biochar in mitigating ammonia volatilization and carbon dioxide emission - Ahmed Alarefee, Hamed; Ishak, Che Fauziah; Othman, Radziah; Karam, Daljit Singh (Elsevier, 2023)
Nitrogen-rich materials such as poultry litter (PL) contributes to substantial N and C loss in the form of ammonia (NH3) and carbon dioxide (CO2) during composting. Biochar can act as a sorbent of ammonia (NH3) and CO2 emission released during co-composting. Thus, co-composting poultry litter with rice husk biochar as a bulking agent is a good technique to mitigate NH3 volatilization and CO2 emission. A study was conducted to evaluate the effects of composting the mixtures of poultry litter with rice husk biochar at different ratios on NH3 and CO2 emissions. Four mixtures of poultry litter and rice husk biochar at different rate were composted at 0:1, 0.5:1, 1.3:1 and 2.3:1 ratio of rice husk biochar (RHB): poultry litter (PL) on a dry weight basis to achieve a suitable C/N ratio of 15, 20, 25, and 30, respectively. The results show that composting poultry litter with rice husk biochar can accelerate the breakdown of organic matter, thereby shortening the thermophilic phase compared to composting using poultry litter alone. There was a significant reduction in the cumulative NH3 emissions, which accounted for 78.38%, 94.60%, and 97.30%, for each C/N ratio of 20, 25, and 30. The total nitrogen (TN) retained relative was 75.96%, 85.61%, 90.24%, and 87.89% for each C/N ratio of 15, 20, 25, and 30 at the completion of composting. Total carbon dioxide lost was 5.64%, 6.62%, 8.91%, and 14.54%, for each C/N ratio of 15, 20, 21, and 30. In addition, the total carbon (TC) retained were 66.60%, 72.56%, 77.39%, and 85.29% for 15, 20, 25, and 30 C/N ratios and shows significant difference as compared with the initial reading of TC of the compost mixtures. In conclusion, mixing and composting rice husk biochar in poultry litter with C/N ratio of 25 helps in reducing the NH3 volatilization and CO2 emissions, while reducing the overall operational costs of waste disposal by shortening the composting time alongside nitrogen conservation and carbon sequestration. In formulating the compost mixture with rice husk biochar, the contribution of C and N from the biochar can be neglected in the determination of C/N ratio to predict the rate of mineralization in the compost because biochar has characteristic of being quite inert and recalcitrant in nature.